The Chongqing Adolescent Twin Study: An Integrative Multimodal Brain Imaging and Non-imaging Dataset - Yanting Zhu; Yixiao Fu; Jiajia Han; Ruoming Wang; Xingshun Ma; Xiaomei Hu; Tao Li; Zhiwei Ma (Scientific Data)
Abstract Adolescence is a pivotal phase of rapid brain development shaped by genetic and environmental factors, offering a critical window for identifying early indicators of psychiatric disorders. The Chongqing Adolescent Twin Study (CATS) explores genetic and environmental influences in 136 typically developing twins aged 12 to 19. This dataset includes multimodal MRI scans (structural, resting-state functional, and diffusion MRI) alongside extensive questionnaires on cognitive abilities, emotional and social behaviors, familial and parenting dynamics, sleep wellness, stress, anxiety, and depression. We describe the dataset in detail and systematically assess its quality. When benchmarked against the Lifespan Human Connectome Project Development (HCP-D) dataset, CATS meets or exceeds HCP-D standards in signal quality, tissue contrast, image sharpness, and head motion control. Preprocessing and imaging phenotype extraction facilitate broad reuse, and high phenotype correlations with HCP-D confirm reliability. This high-quality, multimodal resource provides a unique opportunity to investigate how genetic and environmental factors, along with age-related changes, shape adolescent brain structure, connectivity, and behavior, offering critical insights for precision medicine and early interventions in psychiatry.